Scintillator energy resolution and a way to improve it by kinetic waveform analysis. (March 2019) - Gektin, Aleksandr; Vasil'ev, Andrey
Abstract: The energy resolution of scintillators is examined in view of the distribution of excitation density in the track region, quenching of emission in regions with high concentration of excitations, and appearance of delayed photons from the regions with low concentrations of excitations. The way to improve energy resolution based on weighting of signals from different decay intervals is discussed. Highlights: The expression for energy resolution of scintillators is re-examined. Model of the distribution of excitation density in the track region is used. Fluctuations and kinetics are different for high, medium and low concentration of excitations. Weighting of signals from different decay intervals can improve energy resolution.